Robust audio steganography via genetic algorithm - Zamani, Mazdak (Institute of Electrical and Electronics Engineers, 2009)
Steganography is a technique used to transmit hidden information by modifying an audio signal in an imperceptible manner. The transmission must be possible in spite of subsequent imperceptible alterations (attacks) of the modified signal. We propose a novel approach of substitution technique of audio steganography. Using genetic algorithm, message bits are embedded into multiple, vague and higher LSB layers, resulting in increased robustness. The robustness specially would be increased against those intentional attacks which try to reveal the hidden message and also some unintentional attacks like noise addition as well.